2019
DOI: 10.15408/es.v11i2.10466
|View full text |Cite
|
Sign up to set email alerts
|

Trend in Biology Education Research From 2012 to 2017: A Content Analysis of Papers in Selected Journals From Indonesia

Abstract: subjek penelitian, metode/desain penelitian, elemen penelitian, alat pengumpul data, jenis dan ukuran sampel dan teknik analisis data. Data yang telah diperoleh, telah dianalisis dengan statistik deskriptif dan telah ditampilkan dalam bentuk tabel dan grafik. Kesimpulan penelitian ini adalah tren penelitian di bidang penelitian pendidikan biologi di Indonesia sepanjang tahun 2012-2017 dibedakan menjadi tujuh kategori yaitu topik biologi adalah bentuk dan fungsi hewan, subjek penelitian adalah pengajaran dan pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Cognitive and psychomotor factors were the most frequently used elements, whereas the affective factors got less attention. is finding was consistent with the research results of Haviz and Ridho [36] and S ¸eyda and Sözbilir [37]. e majority of the studies evaluated the effectiveness of students' conceptual knowledge by utilizing various inquiry-based learning strategies.…”
Section: Discussionsupporting
confidence: 89%
“…Cognitive and psychomotor factors were the most frequently used elements, whereas the affective factors got less attention. is finding was consistent with the research results of Haviz and Ridho [36] and S ¸eyda and Sözbilir [37]. e majority of the studies evaluated the effectiveness of students' conceptual knowledge by utilizing various inquiry-based learning strategies.…”
Section: Discussionsupporting
confidence: 89%
“…There are many studies that examine research trends in Indonesia, especially those related to learning biology. As done by M. Haviz (2019) which examines research trends in biology journals but does not specialize in certain topics. Then the trend of research on critical thinking skills (Susetyarini & Fauzi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The effect on achievement is at the highest position (69.9%), followed by the comparison of methods and attitude. So is the result of articles particularly related to biology education that were published specifically in the Biology Education journal in Indonesia (Haviz & Ridho, 2019). They revealed that BER element related to skill aspect was only 15%.…”
Section: Introductionmentioning
confidence: 99%